Oxford illustrated encyclopedia: Vol.6 - Invention and technology (Oxford Univ. Press, 1993)
The book presents a broad conspectus of modern technology, with an international outlook: agriculture based on a high degree of mechanization, the electricity supply, radio and television, air and road transport, and information storage and retrieval follow much the same general pattern